الفنون البيانية في شعر عبد الله بن المعتز: دراسة وصفية وتحليلية - Munadilatul Iezzah binti Ganden Lubis (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Ibnu Muktaz is considered a pioneer in science of Arabic rhetorical. He had a distinctive and versatile style in the analogy, and proficiency in the arts of different Arabic rhetorical. This is shown through his Diwan which is famously stated in Arabic rhetorical industry especially in descriptions, similes and metaphors which are based on knowledge of Arabic rhetorical studies. During his time, he was a figure in the science of Arabic rhetorical and his poems about rhetoric and criticism studies are found in books throughout the Arab cultural history till it was said that he was the most inspiring person in arts of similes and descriptions. The research focuses on the life of Ibnu Muktaz, his teachers and his students. The study wants to see the impact of his literary writing. It also focuses on the unique methods of rhetorical arts deal in his poetry. Thus, the research presents some poetic models that explain it all. The research also aims to further focus on the role of Ibnu Muktaz in the science of Arabic rhetorical, the great impact of his study in Arab poetry, and the characteristics of his poetry. The research also aims to highlight his school in the rhetorical study. In addition, the research displays the different colours of rhetorical arts that characterize him as one of the pioneers of Arabic rhetoric study, through his concern in patterns and images in all his poetry. The research presents these various aesthetic positions through his Diwan which places Ibnu Muktaz as a well-known writer in Arabic rhetorical studies. The research found that Ibnu Muktaz has contributed in two areas which are semantics and Arabic rhetorical studies, and the most special thing in poetry is the different colours of rhetorical arts.